ACUTE FATTY LIVER IN PREGNANCY - Soe, Lwin; Myat, San Yi; Haris Njoo, Suharjono; Tin, Moe Nwe (2020)
Acute fatty liver of pregnancy (AFLP) is an obstetric emergency and life threatening condition of the pregnancy. It affects during last trimester of pregnancy and occasionally occurs in postpartum period. It is presented with malaise, nausea, vomiting, and epigastric pain followed by jaundice. Laboratory tests usually derange liver and renal functions with coagulopathy. The incidence of AFLP is approximately 1 in 15,000 pregnancies. We reported the case of a 34-year-old patient, with multiple pregnancy at 35 weeks of gestation presented with dizziness, headache and dyspepsia aggravated by lying down and noted jaundice during operation. She had postpartum haemorrhage after the operation due to coagulopathy and her laboratory investigations findings favoured to diagnosis as AFLP and treated with supportive management at intensive care unit (ICU). Therefore obstetrician must be aware of one of this hepatic problem in pregnant women at latetrimester.